Inequalities and artificial intelligence - Tiribelli, Simona (Filosofia Morale/Moral Philosophy, 2023)
This paper focuses on one of the most urgent risks raised by artificial intelligence (AI), that is, the risk of AI perpetuating or exacerbating unfair social inequalities. Specifically, this paper argues for the need of decolonizing ethical principles underpinning current AI design through relational theories in order to overcome the current limits of an oversimplified and mainstream mainly Western understanding of ethics in AI, which is hampering the design of AI systems as forces for a fairer and more just society.